Alternative complement pathway assessment in patients with atypical HUS - Roumenina, Lubka T.; Loirat, Chantal; Dragon-Durey, Marie-Agnes; Halbwachs-Mecarelli, Lise; Sautes-Fridman, Catherine; Fremeaux-Bacchi, Veronique (Journal of immunological methods, 2011)
The atypical Hemolytic Uremic Syndrome (aHUS) is a rare thrombotic microangiopathy leading to end stage renal disease in approximately 60% of patients. Over the last decade, a clear link has been demonstrated between this disease and defective complement regulation. The hallmark of the aHUS is the association with mutations in complement alternative pathway genes. Endothelial damage is related to complement dysregulation, but the exact mechanism is just starting to be elucidated. Screening for and characterization of mutations in the components of the C3 convertase (C3 and FB) or its regulators (FH, FI, MCP, and Thrombomodulin) or anti-FH antibodies has become an indispensable part of the disease's diagnostic. This review will initially summarize current knowledge on the understanding of complement activation and regulation, followed by a description on the genetic analysis as well as the methods used for complement protein quantification. Another part of this review will focus on the mechanisms of action of aHUS-associated mutations. We will emphasize on when and why some mutations lead to protein deficiency, while others result in — to dysfunctional but normally expressed proteins. Finally, we will discuss how the therapy of aHUS patients can be modified according to the functional consequences of each particular genetic defect.